Isolation and Analysis of Plasma-Derived Exosomes in Patients With Glioma - Cumba Garcia, Luz M.; Peterson, Timothy E.; Cepeda, Mario A.; Johnson, Aaron J.; Parney, Ian F. (Frontiers in Oncology, 2019)
Gliomas including glioblastoma (GBM) are the most common primary malignant brain tumors. Glioma extracellular vesicles (EVs) including exosomes have biological effects (e.g. immunosuppression) and contain tumor-specific cargo that could facilitate liquid biopsies. We aimed to develop a simple, reproducible technique to isolate plasma exosomes in glioma patients. Glioma patients’ and normal donors’ plasma exosomes underwent brief centrifugation to remove cells/debris followed by serial density gradient ultracentrifugation (DGU). EV size/concentration was determined by nanoparticle tracking. Protein cargo was screened by array, western blot, and ELISA. Nanoscale flow cytometry analysis quantified exosome and microvesicle populations pre- and post-DGU. One-step DGU efficiently isolates exosomes for nanoparticle tracking. Wild type isocitrate dehydrogenase glioma patients’ (i.e more aggressive tumors) plasma exosomes are smaller but higher concentration than normal donors. A second DGU efficiently concentrates exosomes for subsequent cargo analysis but results in vesicle aggregation that skews nanoparticle tracking. Cytokines and co-stimulatory molecules are readily detected but appeared globally reduced in GBM patients’ exosomes. Surprisingly, immunosuppressive programmed death-ligand 1 (PD-L1) is present in both patients’ and normal donors’ exosomes. Nanoscale flow cytometry confirms efficient exosome (<100nm) isolation post-DGU but also demonstrates increased microvesicles (>100nm) in GBM patients’ plasma pre-DGU. Serial DGU efficiently isolates plasma exosomes with distinct differences between GBM patients and normal donors, suggesting utility for non-invasive biomarker assessment. Initial results suggest global immunosuppression rather than increased circulating tumor-derived immunosuppressive exosomes, though further assessment is needed. Increased glioma patients’ plasma microvesicles suggest these may also be a key source for biomarkers.